Perancangan Sistem Pengambilan Keputusan Pengadaan Dan Pemusnahan Buku Perpustakaan Dengan Metode Simple Additive Weighting (Studi Kasus Perpustakaan Fakultas Teknik Universitas Sebelas Maret Surakarta - Kristanto, Widi (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
The mechanism for procuring library materials at the Library of the Faculty of Engineering, Universitas Sebelas Maret Surakarta (UNS) still uses the manual method. This manual method in its process cannot meet the needs for new books according to the interests of library members. In addition, officers also had difficulty determining which books should be destroyed because their economic life had expired and they were rarely borrowed. From these problems the author wants to analyze the destruction and procurement of library materials needed by library members using the Simple Additive Weighting (SAW) method. This analysis is useful for librarians to obtain information on the procurement of new library materials according to the needs of library members, as well as the destruction of library materials that are not in demand. Therefore we need an application that can determine what library materials to buy, and what library materials to destroy so that library materials are more useful for library members in a certain period. The application is designed by the author using the PHP Native programming language and MySQL database. The method used to design the system uses the Software Development Life Cycle (SDLC) with the Waterfall model